2017
DOI: 10.1159/000477930
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Cervical Length Measurement to Reduce Length of Stay in Patients Admitted for Threatened Preterm Labor: A Randomized Trial

Abstract: Objective: To study whether knowledge of cervical length (CL) is useful in reducing the length of hospital stay in women admitted because of threatened preterm labor. Methods: We performed a single-center, parallel, randomized trial at the Hospital Clínic of Barcelona. Inclusion criteria were single pregnancy, gestational age (GA) between 24+0 and 35+6 weeks, Bishop score <6, no parturition within 24-48 h after admission, and no clinical signs of chorioamnionitis, vaginal bleeding, or non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…20 Another individual study that randomized physicians to the knowledge of CL/fFN versus standard care (no knowledge of CL/fFN) reported that physician knowledge that the cervix was long (CL > 30 mm) shortened the time of evaluation for PTL. 9 Most recently, a randomized trial demonstrated reduced length of stay (3 vs. 4 days) with the use of CL ultrasound in PTL evaluation 21 ( Table 3 ). Finally, a cost-effectiveness study from the Netherlands compared various PTL management strategies including universally treating all who present with PTL versus selectively treating based on CL/fFN and found that the most cost-effective strategy for the treatment of PTL was when CL was <15 mm or when CL was 15 to 30 mm and fFN was positive.…”
Section: Discussionmentioning
confidence: 99%
“…20 Another individual study that randomized physicians to the knowledge of CL/fFN versus standard care (no knowledge of CL/fFN) reported that physician knowledge that the cervix was long (CL > 30 mm) shortened the time of evaluation for PTL. 9 Most recently, a randomized trial demonstrated reduced length of stay (3 vs. 4 days) with the use of CL ultrasound in PTL evaluation 21 ( Table 3 ). Finally, a cost-effectiveness study from the Netherlands compared various PTL management strategies including universally treating all who present with PTL versus selectively treating based on CL/fFN and found that the most cost-effective strategy for the treatment of PTL was when CL was <15 mm or when CL was 15 to 30 mm and fFN was positive.…”
Section: Discussionmentioning
confidence: 99%
“…Our results correlate with what is already known in the literature regarding women with SCS. SCS is a well‐known risk factor for PTB, as summarized in a recent Cochrane meta‐analysis, 12 and in additional trials 16,17 . However, data are conflicting regarding the clinical significance of an accidental mid‐trimester finding of ACS in women without risk factors for PTB.…”
Section: Discussionmentioning
confidence: 99%
“…Alfirevic et al 136 . used a cut‐off of 15 mm to guide the decision between active and conservative management, while Palacio et al 137 . opted to use CL ≥ 25 mm as the limit above which a patient could be discharged safely.…”
Section: Ultrasound In the Management Of Singleton Pregnancy With Sym...mentioning
confidence: 99%
“…Ness et al 135 used TVS CL cut-offs of < 20 mm for treatment and > 30 mm for discharge from hospital, adding fetal fibronectin (FFN) as a support tool in cases with CL between 20 and 29 mm. Alfirevic et al 136 used a cut-off of 15 mm to guide the decision between active and conservative management, while Palacio et al 137 opted to use CL ≥ 25 mm as the limit above which a patient could be discharged safely. A meta-analysis of 25 studies 138 reported that, for birth within 7 days from presentation, using TVS CL cut-offs of < 15 mm vs < 20 mm, the sensitivity was 59.9% (95% CI, 52.7-66.8%) vs 75.4% (95% CI, 66.6-82.9%), specificity was 90.5% (95% CI, 89.0-91.9%) vs 79.6% (95% CI, 77.1-81.9%), positive likelihood ratio (LR) was 5.71 (95% CI, 3.77-8.65) vs 3.74 (95% CI, 2.77-5.05) and negative LR was 0.51 (95% CI, 0.33-0.80) vs 0.33 (95% CI, 0.15-0.73).…”
Section: Cervical-length Cut-off For Clinical Decision-making In Symp...mentioning
confidence: 99%